Kinetika reaksi esterifikasi gliserol monoacetin dari gliserol hasil samping industri biodiesel dan asam asetat dengan katalisator lewatit monoplus s-100 - Anita Arsyad; Hary Sulistyo; Sarto Sarto (Jurnal Rekayasa Proses, 2015)
Biodiesel is one of the potential candidates for alternative energy to replace fossil fuel. Glycerol is the side product in biodiesel production. To increase the economic value, glycerol can be processed through esterification to produce glycerol monoacetine. Monoacetine is very useful for non-food application such as printing ink, plasticizer, and intermediate material for biodegradable polyester. This research was conducted in batch reactor with variations of reaction temperatures (323 K-343 K), catalyst concentrations (3%, 5%, and 7% w/w of glycerol), and reactant ratios in terms of glycerol and acetate volume ratios (3:1, 5;1, and 7:1). Samples were withdrawn every 15 minutes up to 60 minutes of reaction time and the free fatty acid concentration was measured. Besides, the initial acid concentration and free glycerol in the raw material were also measured. The highest conversion was obtain as much as 63.86% at 343K, 7:1 reactant volume ratio (glycerol: acetic acid), and catalyst concentration of 3% of glycerol weight. The reaction kinetics of glycerol mono acetin production was modeled. Two kinetics models were used, which were pseudo-homogeneous catalytic model and heterogeneous catalytic model. Based on experimental data fitting on the models, it turned out that pseudo-homogeneous model was better representing the esterification of glycerol with Lewatit Monoplus s-100 catalyst.